Endocrine treatment for breast cancer patients revisited—history, standard of care, and possibilities of improvement - Nabieva, Naiba; Fasching, Peter (Cancers, 2021)
Purpose of review: Due to the findings of current studies and the approval of novel substances for the therapy of hormone-receptor-positive breast cancer patients, the established standards of endocrine treatment are changing. The purpose of this review is to give an overview of the history of endocrine treatment, to clarify its role in the present standard of care, and to discuss the possibilities of improvement. Recent findings: Tamoxifen, aromatase inhibitors, and fulvestrant are the main drugs that have been used for decades in the therapy of hormone-receptor-positive breast cancer patients. However, since a relevant number of women suffer at some point from disease recurrence or progression, several novel substances are being investigated to overcome resistance mechanisms by interfering with certain signaling pathways, such as the PI3K/AKT/mTOR or the CDK4/6 pathways. mTOR and CDK4/6 inhibitors were the first drugs approved for this purpose and many more are in development. Summary: Endocrine treatment is one of the best tolerable cancer therapies available. Continuous investigation serves to improve patients’ outcomes and modernize the current standard of care. Considering the resistance mechanisms and substances analyzed against these, endocrine treatment of hormone-receptor-positive breast cancer is on the brink of a new era.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Abemaciclib; Alpelisib; Aromatase inhibitor; Breast cancer; CDK 4/6 in-hibitor; Compliance; Endocrine treatment; Fulvestrant; MTOR inhibitor; Palbociclib; PI3K inhibitor; Ribociclib; SERD; Tamoxifen